Pemberdayaan Ibu Rumah Tangga Kelurahan Tangkerang Tengah Melalui Pelatihan Pembudidayaan Tanaman Dapur Hidup - Enny Murtryarny; Vonny Indah Sari; Muhammad Rizal (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Dapur Hidup is a way of using yard land to grow plants for kitchen needs. Besides being economical, growing live kitchen plants in the yard of the house is also guaranteed to be healthy. Plants grown themselves, of course, do not contain chemicals such as pesticides and other harmful compounds. This community service activity aims to provide knowledge to housewives on how to do good cultivation of dapur hidup plants to provide benefits such as being able to green the yard to make it look more comfortable and beautiful, when it is produced it can be used for members in need. This kind of thing is a means to provide an example and motivation for members to want to use their respective yards to plant a living kitchen such as chili, eggplant, tomatoes, and other crops so that the results can help the family's kitchen needs. This activity hopes that housewives will be motivated to provide dapur hidup plants in their respective yards. The results of this activity showed that there was an increase in community knowledge about how to grow live kitchen plants. The results of the questionnaires that were distributed showed that the increase in participants' knowledge increased by 100% after the training.